Nematodes from saline and freshwater lakes of the Vestfold Hills, East Antarctica, including the description of Hypodontolaimus antarcticus sp. n. - Andrássy, I.; Gibson, J. A. E. (Polar Biology, 2007)
The invertebrate fauna of many Antarctic ice-free areas, even those close to permanent research stations, can be poorly known. Here we describe some nematodes from freshwater and saline, marine-derived lakes of the Vestfold Hills, East Antarctica. The freshwater lakes contained the widespread East Antarctic endemic species, Plectus frigophilus Kirjanova, 1958. The saline lakes were inhabited by two recently described species, Halomonhystera halophila Andrássy, 2006 and Halomonhystera continentalis Andrássy, 2006, and by a new species described in this report, Hypodontolaimus antarcticus sp. n. Originally marine but now brackish Highway Lake contained a nematode fauna with both freshwater and marinederived components. The nematode fauna of Antarctica now consists of 54 named species, 22 of which are found in East Antarctica.
NeMys doc_id: 17773 NeMys doc_id: 16862